Retrieving plasmonic near-field information: A quantum-mechanical model for streaking photoelectron spectroscopy of gold nanospheres - Li, Jianxiong; Saydanzad, Erfan; Thumm, Uwe (My University, 2016)
Streaked photoemission from nanostructures is characterized by size-and material-dependent nanometer-scale variations of the induced nanoplasmonic response to the electronic field of the streaking pulse and thus holds promise of allowing photoelectron imaging with both subfemtosecond temporal and nanometer spatial resolution. In order to scrutinize the driven collective electronic dynamics in 10-200-nm-diameter gold nanospheres, we calculated the plasmonic field induced by streaking pulses in the infrared and visible spectral range and developed a quantum-mechanical model for streaked photoemission by extreme ultraviolet pulses. Our simulated photoelectron spectra reveal a significant amplitude enhancement and phase shift of the photoelectron streaking trace relative to calculations that exclude the induced plasmonic field. Both are most pronounced for streaking pulses tuned to the plasmon frequency and retrace the plasmonic electromagnetic field enhancement and phase shift near the nanosphere surface.
Citation: Li, J. X., Saydanzad, E., & Thumm, U. (2016). Retrieving plasmonic near-field information: A quantum-mechanical model for streaking photoelectron spectroscopy of gold nanospheres. Physical Review A, 94(5), 5. doi:10.1103/PhysRevA.94.051401
Keywords: Nanoparticles; Optics; Physics